The role of knowledge in valuation practice: expert valuers' perceptions. Issue 6 (11th June 2019) - Amidu, Abdul-Rasheed; Boyd, David; Agboola, Alirat Olayinka
Abstract : Purpose: The purpose of this paper is to explore the role knowledge plays in expert commercial valuer practice to unpack the way theoretical and experiential knowledge operates in order to improve practice and education. Design/methodology/approach: Adopting a cognitivist perspective and identifying meta-reasoning, using a grounded theory methodology, through the study of 11 chartered valuation surveyors practicing in Birmingham, United Kingdom, the distinctive theoretical and experiential knowledge they used was elicited through their in-depth reflection on a valuation task followed by analytical interviews exploring meaning and reasons of actions described. Findings: The results confirmed that multi-sourced and rich valuation knowledge was a key attribute of a valuation expert. However, the experiential knowledge was not used to undertake the task but to select the methods and knowledge appropriate for the task and context. This meta-reasoning is a key to the speed, accuracy and justification of their practices. Thus, the experience gained from many years of valuation provides expert valuers with meta-reasoning involving knowledge of what, how and when to deal with problems in different circumstances such as the knowledge of markets and handling of clients. Practical implications: Making meta-reasoning a key aspect of valuation will identify its characteristics more clearly, thus assisting the development of practitioners and providing a new focus for education to advance professional goals. Originality/value: Meta-reasoning and meta-cognitive knowledge have not been identified as a key to successful valuation practice. This meta-reasoning allows a subtle balance of theory and experience in valuation practice that is appropriate to the situation.